2017
DOI: 10.1007/s10637-017-0507-3
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of patients with sorafenib-treated advanced hepatocellular carcinoma eligible for second-line treatment

Abstract: Background Regorafenib has been investigated for its efficacy and safety as a second-line treatment in patients with advanced hepatocellular carcinoma (HCC). We assessed the characteristics of patients with HCC treated with sorafenib who might be eligible for second-line treatment in general and regorafenib in particular. Methods Patients with HCC treated with sorafenib were retrospectively analyzed. We defined second-line candidate patients as maintaining Child-Pugh A and ECOG-PS ≤1 at the time of sorafenib f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
47
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 30 publications
6
47
1
2
Order By: Relevance
“…Both good liver function (Child–Pugh A) and good general condition (ECOG‐PS score of 0 or 1) were adopted as essential inclusion criteria in clinical trials that clarified the efficacy of almost all new systemic chemotherapeutic agents in HCC patients . The number of candidates for second‐line treatments after sorafenib failure was reported to range from 50.3% to 70.0% . Similarly, in our study, the proportion of candidates for second‐line treatments at first radiologic PD was 57.3%.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Both good liver function (Child–Pugh A) and good general condition (ECOG‐PS score of 0 or 1) were adopted as essential inclusion criteria in clinical trials that clarified the efficacy of almost all new systemic chemotherapeutic agents in HCC patients . The number of candidates for second‐line treatments after sorafenib failure was reported to range from 50.3% to 70.0% . Similarly, in our study, the proportion of candidates for second‐line treatments at first radiologic PD was 57.3%.…”
Section: Discussionsupporting
confidence: 52%
“…The reasons for ineligibility were deterioration of liver function (Child–Pugh B or C) in 38.8% and worsening of general condition (ECOG‐PS score ≥ 2) in 23.3%; these factors, in addition to tolerance to sorafenib treatment, comprised the eligibility criteria for regorafenib treatment, according to the RESORCE trial . The number of candidates eligible for regorafenib treatment was reported as 30.6–44.2%, and the rate of the intolerability to sorafenib was reported as 32.0–53.7% . In our study, the proportion of candidates for regorafenib treatment at radiologic PD was 35.0%, and the most common reason for classification into the RESORCE‐out group was intolerability to sorafenib (42.7%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There has been only one report [4] regarding the proportion of patients meeting the eligibility criteria for the RESORCE trial at radiological PD. The authors reported that, among 185 patients who failed sorafenib treatment and had both Child-Pugh class A and an ECOG-PS score of 0 or 1 at the time of sorafenib failure, and a starting sorafenib dose of 800 mg/day, 69 patients (37.0%) were candidates for regorafenib at the time of sorafenib failure.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in patients refractory to so­ra­fenib, postprogression survival (PPS) is expected to improve by switching from sorafenib to regorafenib [2, 3]. However, not all patients who have confirmed radiological PD can switch to regorafenib therapy, because the efficacy and safety of regorafenib administration in patients who do not meet the eligibility criteria for the RESORCE trial have not been verified [4]. According to the Clinical Practice Guidelines for Hepatocellular Carcinoma 2017 in Japan and the Barcelona Clinic Liver Cancer (BCLC) Guidelines for Hepatocellular Carcinoma 2018, it is recommended that regorafenib should be indicated for patients tolerant to sorafenib and with well-preserved liver function (Child-Pugh class A) as second-line treatment after radiological PD with sorafenib.…”
Section: Introductionmentioning
confidence: 99%